Enhancing the Load-bearing Capacity of a Damaged Hydraulic Structure Rehabilitated by Underwater Concreting - Thi, Bach Phuong Ho; Nguyen, Viet Duc; Vuong, Quoc Vu; Dang, Hoang Minh (Engineering, Technology & Applied Science Research, 2024)
Due to the severe environment, damages often occur early on hydraulic structures, even in parts submerged in water. This paper presents a study on how the load-bearing capacity of the hydraulic structure is enhanced, once it has been rehabilitated by underwater concreting. A column has been considered as the hydraulic structure. The damaged part of the column was submerged in water, hence, it was repaired by the underwater concrete. For this, the tremie casting method was taken into account. The compression test results pointed out that the damaged column after rehabilitation had a similar load-bearing capacity to the undamaged column, while the not rehabilitated column had reduced load-bearing capacity by 20%. The failure mode of the damaged column after the rehabilitation presented longitudinal cracks along the body of the column, which is similar to that occurred in the undamaged column. Besides, there was no sign of delamination between the protective layer and the existing concrete of the damaged column, proving the feasibility of the selected casting method and concrete mixture for rehabilitation.